(untitled) (Khairulummah, 2023)
In the Arabic language, “Qira’at” encompasses both recitation and verbal expression. It refers not only to the act of reciting but also to the spoken or written word. In the realm of Islamic terminology, “Qira’aat” specifically denotes the variations in the wording of the Qur’anic revelation, particularly in the pronunciation of individual letters. The study of these recitations constitutes a distinct field of inquiry, focusing on the nuanced differences in how the Holy Qur’an is articulated. The foundation of Qur’anic recitations lies in their authenticity, traced back to reliable sources. These diverse recitations introduce variations in the way verses are recited, allowing readers to approach the same text from different angles. Jurists, in turn, derive multiple legal rulings based on these variations. Matters of belief are intricately intertwined with these recitations, impacting theological concepts related to divinity, prophecy, the unseen, and the consequences of human actions. The effect of these differences in Qur’anic readings is palpable and multifaceted. Through this study and analysis, we explore these intricacies, elucidating the impact of various recitations. By delving into multiple examples, we deepen our understanding of the Book of God Almighty and fortify our Islamic beliefs.